Identification of key amino acid residues toward improving the catalytic activity and substrate specificity of plant-derived cytochrome P450 monooxygenases CYP716A subfamily enzyme for triterpenoid production in Saccharomyces cerevisiae - Romsuk, Jutapat; Yasumoto, Shuhei; Seki, Hikaru; Fukushima, Ery Odette; Muranaka, Toshiya (Frontiers in Bioengineering and Biotechnology, 2022)
Triterpenoids constitute a group of specialized plant metabolites with wide structural diversity and high therapeutic value for human health. Cytochrome P450 monooxygenases (CYP) are a family of enzymes important for generating the structural diversity of triterpenoids by catalyzing the site-specific oxidization of the triterpene backbone. The CYP716 enzyme family has been isolated from various plant families as triterpenoid oxidases; however, their experimental crystal structures are not yet available and the detailed catalytic mechanism remains elusive. Here, we address this challenge by integrating bioinformatic approaches with data from other CYP families. Medicago truncatula CYP716A12, the first functionally characterized CYP716A subfamily enzyme, was chosen as the model for this study. We performed homology modeling, structural alignment, in silico site-directed mutagenesis, and molecular docking analysis to search and screen key amino acid residues relevant to the catalytic activity and substrate specificity of the CYP716A subfamily enzyme in triterpenoid biosynthesis. An in vivo functional analysis using engineered yeast that endogenously produced plant-derived triterpenes was performed to elucidate the results. When the amino acids in the signature region and substrate recognition sites (SRSs) were substituted, the product profile of CYP716A12 was modified. We identified amino acid residues that control the substrate contraction of the enzyme (D292) and engineered the enzyme to improve its catalytic activity and substrate specificity (D122, I212, and Q358) for triterpenoid biosynthesis. In addition, we demonstrated the versatility of this strategy by changing the properties of key residues in SRSs to improve the catalytic activity of Arabidopsis thaliana CYP716A1 (S356) and CYP716A2 (M206, F210) at C-28 on the triterpene backbone. This research has the potential to help in the production of desired triterpenoids in engineered yeast by increasing the catalytic activity and substrate specificity of plant CYP716A subfamily enzymes.